Recent advances and perspectives of biochar for livestock wastewater: Modification methods, applications, and resource recovery - Gao, Rong; Ding, Sujuan; Liu, Zhuangzhuang; Jiang, Hongmei; Liu, Gang; Fang, Jun (Journal of environmental chemical engineering, 2024)
Water, a critical resource, confronts significant challenges with respect to its secure utilization and ecological integrity. 0.817 units of drinking water can be saved for every unit of recycled water used, emphasizing the global importance of wastewater recycling for economic and ecological benefits. In poultry production, water consumption per tonne of product varies from 6 to 30 m3, underscoring the significance of recycling livestock wastewater for sustainable development, agricultural efficiency, modernization, and climate change mitigation. The porous structure and surface functional groups of biochar make it a key medium for resource recovery. Utilizing biochar for livestock wastewater treatment can offer both economic and environmental advantages, as it can adsorb certain components from wastewater and transform them into valuable resources. However, there is currently no literature that provides a detailed description of the reuse forms of substances adsorbed and recovered by biochar from livestock wastewater. This paper reviews the utilization of biochar in the treatment of livestock wastewater, with a specific focus on swine wastewater (SW), and outlines future directions for research in the domain of biochar resource recovery. The objective of this review is to heighten awareness of the diverse potential applications of biochar for resource recovery from wastewater, thereby facilitating the further advancement and demonstration of pertinent wastewater treatment technologies. [Display omitted] •Biomagnification heightens the health risks from livestock wastewater.•Biochar needs to be modified to enhance its adsorption properties.•Recycling nutrients from livestock wastewater aids sustainable agricultural progress.•Future research directions for the resource recovery potential of biochar are suggested.